The Effect of Different Concentration of 2-Methyl-4-Chlorophenoxy Acetate Acid on Graphite Oxide Intercalation Nanohybrid - I. Hasanuddin, N.; N. Dzulkifli, N.; A. I. S. M. Ghazali, S. (International Journal of Engineering and Technology, 2018)
In this study, the effect of different concentration of 2-methyl-4-chlorophenoxy acetate acid (MCPA) was investigated to synthesis the successful intercalated herbicide nanohybrid by using graphite oxide (GO) as a nanocarrier. Through this experiment, a well-organized nanohybrid was obtained at the concentration of 0.3 M of MCPA. 2-methyl-4-chlorophenoxy acetate acid- graphite oxide (MCGO) nanohybrid was characterized by using FTIR, PXRD and CHNS. From the results obtained, the expansion of d-spacing of MCGO nanohybrid has indicated the presence of MCPA in the GO interlayer with the loading percentage around 98 %. Besides, FTIR spectra of the nanohybrid shown a resemblance peaks of the MCPA and GO that could confirm the formation of nanohybrid. Furthermore, the controlled release of MCPA into sodium carbonate solution (Na2CO3) was found to be reliant on concentration of Na2CO3 solution.Â Â Â